The Effective Role of Soil Indigenous Fungi on 2.4-D Herbicide Degradation - Abdulridha Taha Sarhan (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
The normal field soil environment safeguarded, via indigenous microbes in a native manner, with the aim of turning herbicide waste into productive bio-resources, through fungi activities. This study aims to determine the effective role of soil indigenous fungi on 2.4-D herbicide degradation. The research was conducted over a period of six weeks, on Iraqi cereal field. A total of eight fungi species, belonging to six genera, (Aspergillus candidus L. ATCC 1002, A. niger T. ATCC 16888, Curvularia lunata W. B1933, Penicillium sp. L. 1809, Rhizopus stolonifer L. B9770, Stachybotrys atra C. 1837, Trichoderma harzianum R. IOC 3844, and T. lignorum T. Hartz 1872), were isolated from the soil. During the exposure periods, fungal populations were differently affected, upon treatments with herbicide. The applied herbicide treatments showed different effects on growth and development of the isolated fungi. The results showed that, five of the eight fungi species (C. lunata B1933, Penicillium sp. 1809, R. stolonifer B9770, T. harzianum IOC 3844, and T. lignorum Hartz 1872) were greatly enhanced by the treatment process. However, two fungi (S. atra 1837, and A. candidus ATCC 1002) were affected negatively by the herbicide, while one (A. niger ATCC 16888) remained unaffected. Once extracted from the soil of wheat fields in Iraq, the fungus S. atra 1837, was first isolated. The highest inhibitory effect was caused by 2.4-D herbicide, on the toxigenic fungus S. atra, causing its disappearance from the field at the last week of application. The laboratory experiments showed similar herbicide effects on the isolated fungi at low and moderate levels, while those at the high level (800 µg/ml) were toxic. These results showed that the herbicide 2.4-D treatments have substantial effects on microbial population in the field. When applied at recommended field rate, the herbicide causes transient impacts on fungal population growth and biodiversity, with the majority of the organism becoming responsible for 2.4-D mineralization in the soil. Therefore, the use of 2.4-D herbicide does not only control weed population, but it also affects microbial activities, especially indigenous fungi in the soil.